Short communication: Apparent efficiency of colostral immunoglobulin G absorption in Holstein heifers - Halleran, Jennifer; Sylvester, Hannah J.; Foster, Derek M. (Journal of dairy science, 2017)
Adequate absorption of bovine colostrum correlates with improved neonatal health. The apparent efficiency of absorption (AEA) of immunoglobulins can be measured using a mathematical equation based on serum and colostral IgG concentration levels, as well as calf body weight and the volume of colostrum being fed. Although commonly measured in research projects, little information is available on the normal AEA across a large group of healthy calves on multiple farms. The purpose of this study was to observe how contributing factors (volume of feeding, birth weight, and time of feeding) can alter AEA and establish a reference range for AEA in healthy calves. Study subjects were 100 Holstein heifer calves from 5 different dairies in North Carolina and Colorado. After a normal calving, the heifer received either 4 or 5.6 L of colostrum within 4 h of birth, an aliquot of the fed colostrum was saved, and a blood sample was collected between 24 and 36 h after birth. Birth weights were measured using the same weight tape on each farm. Radial immunodiffusion assay was performed to obtain IgG concentrations in the colostrum and serum samples. From this data, the AEA was calculated. The AEA ranged from 7.7 to 59.9% with mean of 28.1 ± 9.5% and median of 27.5%. The AEA of 69% of the calves fell between 21 and 40%. The AEA varied widely between calves, even when feeding was standardized. Results suggest that serum IgG concentration may potentially be increased by feeding increased volumes of colostrum or genetic selection, given the wide range of AEA values obtained.